DIGITAL TRANSFORMATION, INNOVATIVE LEADERSHIP, AND ORGANIZATIONAL CULTURE: THEIR ROLE IN IMPROVING EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT - Sunardi, Sunardi; Madiistriyatno, Harries; Suhardi, Suhardi (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study discusses the role of digital transformation, innovative leadership, and organizational culture in improving employee performance with organizational commitment as a mediating variable. Rapidly changing work environments require organizations to adapt through the application of digital technology, creative leadership patterns, and a culture that supports collaboration and innovation. The purpose of the study was to examine the direct and indirect relationship between these variables and see how organizational commitment strengthens existing linkages. The study uses a quantitative approach by involving employees as respondents. The data collection technique is carried out through the dissemination of questionnaires that have been tested for validity and reliability. The results of the analysis show that digital transformation has a positive effect on performance improvement, innovative leadership makes a significant contribution in encouraging morale, and organizational culture is able to strengthen employee behaviour towards a productive direction. Simultaneously, these three variables play an important role in creating better performance. However, organizational commitment does not always successfully mediate the impact of digital transformation, innovative leadership, and organizational culture on performance. This indicates that organizational commitment has a limited role, so there needs to be an additional strategy to strengthen employee loyalty. This research implies that organizations that want to improve employee performance need to balance the application of digital technology, innovative leadership, and a conducive work culture, as well as placing organizational commitment as a supporting factor that must continue to be nurtured on an ongoing basis.